Hypocholesterolemic and antiatherosclerotic potential of Basella alba leaf extract in hypercholesterolemia-induced rabbits - Gunasekaran, Baskaran; Salvamani, Shamala; Azlan, Azrina; Ahmad, Siti Aqlima; Yeap, Swee Keong; Abd. Shukor, Mohd. Yunus (Hindawi Publishing Corporation, 2015)
Hypercholesterolemia is the major risk factor that leads to atherosclerosis. Nowadays, alternative treatment using medicinal plants gained much attention since the usage of statins leads to adverse health effects, especially liver and muscle toxicity. This study was designed to investigate the hypocholesterolemic and antiatherosclerotic effects of Basella alba (B. alba) using hypercholesterolemia-induced rabbits. Twenty New Zealand white rabbits were divided into 5 groups and fed with varying diets: normal diet, 2% high cholesterol diet (HCD), 2% HCD + 10 mg/kg simvastatin, 2% HCD + 100 mg/kg B. alba extract, and 2% HCD + 200 mg/kg B. alba extract, respectively. The treatment with B. alba extract significantly lowered the levels of total cholesterol, LDL, and triglycerides and increased HDL and antioxidant enzymes (SOD and GPx) levels. The elevated levels of liver enzymes (AST and ALT) and creatine kinase were noted in hypercholesterolemic and statin treated groups indicating liver and muscle injuries. Treatment with B. alba extract also significantly suppressed the aortic plaque formation and reduced the intima: media ratio as observed in simvastatin-treated group. This is the first in vivo study on B. alba that suggests its potential as an alternative therapeutic agent for hypercholesterolemia and atherosclerosis.